(untitled) (Biological Sciences - PJSIR, 2024)
Aflatoxins are naturally occurring toxic metabolites produced by several fungi. Aflatoxins are responsible for contamination of animal feed and human food which in turn causes the detrimental effects which mainly includes carcinogenicity, stunted growth, hepatocellular carcinoma and liver cirrhosis. Amongst the aflatoxins, AFB1 is designated as a potent hepatocarcinogen in humans. This study is aimed to detect and detoxify different types of aflatoxins in corn grain collected from Lahore and Kasur, Pakistan. Overall samples (n=80) were collected for the determination of aflatoxins by thin layer chromatography (TLC). The samples collected from Lahore (n=40), the AFB1 was detected in 12 samples (30%) samples, and similarly from Kasur AFB1 was detected in 9 samples (22%). The concentration of AFB1 in samples ranged from 1.51 to 38.54 µg/Kg. The second phase of the study was focussed on the use of different detoxification methods. Various detoxification strategies were used to degrade AFB1 in contaminated corn i.e. physical, chemical and biological method. Maximum reduction in AFB1 level was obtained by using 20% citric acid, which reduced 38.54 µg/Kg to 18.23 µg/Kg (52.6%), mustard oil reduced 38.08 µg/Kg to 18.22 µg/Kg (52.1%) and boiling method reduced 38.54 µg/Kg to 20.91 (45.7%) in corn samples. It can be concluded from the current study that corn is highly susceptible to fungal contamination and produces AFB1 beyond permissible limits. The improvement in storage conditions and use of detoxification methods can help us reduce the fungal contamination and avoid health related risks due to presence of aflatoxins.